2012
DOI: 10.1371/journal.pone.0037281
|View full text |Cite
|
Sign up to set email alerts
|

A Rat Model of Central Venous Catheter to Study Establishment of Long-Term Bacterial Biofilm and Related Acute and Chronic Infections

Abstract: Formation of resilient biofilms on medical devices colonized by pathogenic microorganisms is a major cause of health-care associated infection. While in vitro biofilm analyses led to promising anti-biofilm approaches, little is known about their translation to in vivo situations and on host contribution to the in vivo dynamics of infections on medical devices. Here we have developed an in vivo model of long-term bacterial biofilm infections in a pediatric totally implantable venous access port (TIVAP) surgical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
45
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 59 publications
(46 citation statements)
references
References 45 publications
(57 reference statements)
1
45
0
Order By: Relevance
“…In validating our model, we found that rats required immunosuppression and a high inoculum, consistent with previous reports (76,77,88,89). Following validation, we used the model to assess virulence of the mutant S. epidermidis strains 3 days postinfection.…”
Section: Figsupporting
confidence: 79%
See 1 more Smart Citation
“…In validating our model, we found that rats required immunosuppression and a high inoculum, consistent with previous reports (76,77,88,89). Following validation, we used the model to assess virulence of the mutant S. epidermidis strains 3 days postinfection.…”
Section: Figsupporting
confidence: 79%
“…***, P Ͻ 0.001; **, P Ͻ 0.01; *, P Ͻ 0.05 (n Ն 4 biological replicates). inocula of S. epidermidis from the bloodstream in the absence of a foreign body (76,77), to increase the percentage of catheters seeded following S. epidermidis challenge, rats were given intraperitoneal injections of CP to produce leukopenia. To validate our model and confirm that the presence of a catheter and immunosuppression are critical for S. epidermidis infection, rats were divided into four groups prior to bacterial inoculation: (i) catheter plus CP, (ii) catheter only, (iii) CP only, and (iv) no catheter or CP (no treatment).…”
Section: Figmentioning
confidence: 99%
“…Using a rat model of biofilm-related infection with a totally implantable venous access port (TIVAP), it was recently shown that the gentamicin-EDTA combination was the most effective lock solution compared to gentamicin alone, EDTA alone, or ethanol (70%) (87,344). Gentamicin-EDTA is therefore a potential lock solution able to cure highly tolerant biofilms and eradicate persistent bacteria, thereby preventing recurrence of Gram-positive as well as Gram-negative bacterial biofilms on TIVAP (344).…”
Section: Targeting Biofilm Recalcitrance: Progress and Perspectivesmentioning
confidence: 99%
“…While some studies showed that combinations of different antibiotics are more efficient than single-antibiotic lock solutions (1,9,34), the efficacy of nonantibiotic compounds is currently being investigated to improve lock solutions and reduce the use of antibiotics.…”
mentioning
confidence: 99%